﻿Lettres de Degas à Thérèse Morbilli conservées au Musée des beaux-arts du Canada - Pantazzi, Michael (RACAR : Revue d'art canadienne / Canadian Art Review, 1988)
The archives of the National Gallery of Canada own some unpublished letters that were written by Edgar Degas to one of his sisters, Thérèse Morbilli. Though these letters have been known to exist and occasionally alluded to in print, this article brings them to public attention, in full, for the first time. As such, they join the very small group of published letters from the artist to his family, documents that reveal the more intimate side of his existence and, not least, an unsuspected concern for the welfare of his kin. Degas seldom dated his letters. Inevitably, this idiosyncrasy has affected some of the editors of his published correspondence, making it necessary to revise the tentative dating once ascribed to some of the letters. Thus, the publication of the documents in Canada is accompanied by a revision of the dates of a number of letters from the published corpus of correspondence.